Price of the Soil: Property Values of Leaseholds and Certificates of Possession - Rogers, Steven; Ballantyne, Ceilidh; Tompkins, Erin; Ballantyne, Brian (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2018)
This paper presents the empirical analysis of property values across a sample of 228 leaseholds and 79 Certificates of Possession (CP) on 34 First Nation Reserves. The property values were benchmarked against a sample of 338 fee simple property sales in 34 comparable non-Indigenous communities. The results were that leaseholds were discounted 17-75% (with a mean of 24%) and CPs were discounted 65-98% (with a mean of 88%). Data across 14 factors was used to analyze trends in property values. Three trends were noteworthy: (1) Leasehold values were higher in communities where the community housing score (estimate of the quality of housing) was higher; (2) CP values were higher in communities where the ratio of informality was lower (estimate of the proportion of properties held by formalized rights under the Indian Act); and (3) Property values were higher when Chief and Council remuneration was higher. The steep discounts observed here must spur research into the viability of existing land tenure/registration systems on First Nation Reserves and into the merits of new institutions to serve First Nations.